The New Palgrave Dictionary of Economics and the Law
eReference.
Keywords: A great deal of economics is about law - the functioning of markets, property rights and their enforcement, financial obligations, and so forth - yet these legal aspects are almost never addressed in the academic study of economics. Conversely, the study and practice of law entails a significant understanding of economics, yet the drafting and administration of laws often ignore economic principle. The New Palgrave Dictionary of Economics and the Law is uniquely placed by the quality, breadth and depth of its coverage to address this need for building bridges. Drawn from the ranks of academics, professional lawyers, and economists in eight countries, the 340 contributors include world experts in their fields. Among them are Nobel laureates in economics and eminent legal scholars. First published in 1998 and now available in paperback for the first time, The New Palgrave Dictionary of Economics and the Law has established itself as a classic reference work in this important field.